As mulheres nos Encontros de Arte Moderna de Curitiba/PR (1969-1980) - Bach, Kamila Tatiana da Cruz (2023)
The Encontros de Arte Moderna were events that took place between 1969 and 1980 in a total of 11 editions, with programming in different spaces of Curitiba-PR. To the analyze these events from the perspective of the Dicionário de Artes Plásticas do Paraná, de Adalice Araújo, by Adalice Araújo (1931-2012), it is noted that the author, when speaking of the artists that develop their productions in these events, there is a relevant number of women. The same perspective is not seen in the other two analyzed versions, the book Festa no Vazio: Performance e contracultura nos Encontros de Arte Moderna (2017), by Artur Freitas and the exhibition at the Museu de Arte Contemporânea do Paraná, Encontros de arte moderna, os conceitualismos no Paraná (2011-12), curated by Fernando Bini. Thus, around the themes History of women and History of art in Curitiba-PR, the question arises: In the 1970s in Curitiba, how the circulation and performance of women in the productions of the artistic circuit of the city? The research is justified by the need to develop and expand research in the area of women’s history, historically left to the margins in art research, and to expand studies on history and art development in Curitiba-PR.